(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Human health cannot be bought with any amount of wealth and money. In a democratic society, where each person is considered responsible for his or her own behavior, human health is elevated to the level of a supreme value of paramount importance. We can say that words, thoughts, intentions, and actions are the basis for a person’s moral and aesthetic activities and goals and aspirations towards achieving moral beauty, which are the basis for the correct functioning of a person.